Combination of palbociclib and radiotherapy for glioblastoma - Whittaker, Shane (Cell Death Discov, 2017)
The cyclin-dependent kinase inhibitor, palbociclib has shown compelling efficacy in breast cancer patients. Several pre-clinical studies of glioblastoma (GBM) have also shown palbociclib to be efficacious. In this study, we investigated palbociclib in combination with radiation therapy (RT) for treating GBM. We tested palbociclib (with and without RT) on four patient-derived cell lines (PDCLs; RB1 retained; CDKN2A loss). We investigated the impact of therapy on the cell cycle and apoptosis using flow cytometry, in vitro. Balb/c nude mice were intracranially injected with the PDCL, GBM-L1 and treated orally with palbociclib (with and without RT). Overall survival was measured. Palbociclib treatment resulted in a significant increase in the percentage of cells in the G1 cell cycle phase. Apoptotic cell death, measured by Annexin V was induced. Palbociclib combined with RT acted synergistically with the significant impediment of colony formation. The oral treatment of mice with palbociclib did not show any significant survival advantage when compared to control mice, however when combined with RT, a survival advantage of 8 days was observed. Our results support the use of palbociclib as an adjuvant treatment to RT and warrant translation to the clinic.